THE ROLE OF ARTIFICIAL INTELLIGENCE IN TEACHING ENGLISH AS A FOREIGN LANGUAGE (Universal International Scientific Journal, 2026)
This article examines the growing role of artificial intelligence (AI) in teachingEnglish as a foreign language (EFL). With the rapid development of digital technologies, AI hasbecome an important tool in modern education. The study focuses on how artificial intelligencesupports English language teaching by enhancing grammar, vocabulary, reading, and writing skills.Additionally, the article highlights the advantages and challenges of integrating AI into EFLclassrooms and emphasizes the importance of using AI as a supplementary tool rather than areplacement for teachers. The findings suggest that AI can significantly improve the quality andeffectiveness of EFL instruction when used appropriately.
Keywords: Artificial intelligence; EFL; English language teaching